Ocean glider observations of iceberg-enhanced biological production in the northwestern Weddell Sea - Biddle, Louise C.; Kaiser, Jan; Heywood, Karen J.; Thompson, Andrew F.; Jenkins, Adrian (Geophysical Research Letters, 2015)
Icebergs affect local biological production around Antarctica. We used an ocean glider to observe the effects of a large iceberg that was advected by the Antarctic Slope Current along the continental slope in the northwestern Weddell Sea in early 2012. The high-resolution glider data reveal a pronounced effect of the iceberg on ocean properties, with oxygen concentrations of (13±4) μmolkg-1 higher than levels in surrounding waters, which are most likely due to positive net community production. This response was confined to three areas of water in the direct vicinity of the iceberg track, each no larger than 2 km2. Our findings suggest that icebergs have an impact on Antarctic production presumably through local micronutrient injections, on a scale smaller than typical satellite observations of biological production in the Southern Ocean.